Transforming Foundation Phase Life Skills Teachers’ Use of Learning and Teaching Support Materials Towards Sustainable Development of Teaching - Nqabeni, Pelokazi (Research in Social Sciences and Technology- OpenED Network, 2024)
This paper reports on transforming Foundation Phase teachers’ use of learning and teaching support materials (LTSMs) to sustain teaching and learning in Life Skills classrooms. This paper aimed to comprehend teachers’ perspectives on how they could transform their practices using LTSMs to improve their teaching and learner performance to contribute towards the sustainable development of teaching. The National Policy and Guidelines for LTSM stipulate that teachers must be teaching mediators. The study was informed by an analytical framework for studying classroom practices along the Activity Theory (AT) dimensions through teachers’ and learners’ interactions. The case study design was qualitative with an interpretive paradigm. Purposive sampling gathered information from three Grade 3 Life Skills teachers through semi-structured interviews, structured observations, and document analysis. Data were analysed, and themes emerged from the questions. Findings revealed that LTSMs are ineffective in improving teaching and learner performance due to shortages, overcrowded classrooms, and lack of professional development. We recommend that the Department of Education should provide more classrooms to assist teachers in their practices. Also, there should be more professional development activities for teachers to transform their practices for sustainable development.